Basic education in Communist Hungary. A commons approach. Issue 2 (August 2014) - Gyuris, Ferenc
In commons research, the study of the 'knowledge commons' has emerged as a new field of interest over the last few years. Our paper begins by providing a brief overview of the state of research in the field, and proceeds by discussing some crucial but relatively underconceptualised issues. The difference between information and knowledge, and the ambiguities surrounding the claim that all sorts of knowledge can be considered part of the commons, are the focal point here. We also pay close attention to education, arguing that it is not a common good, but rather a common-pool resource institution that ensures that some forms of knowledge can be governed as a commons. With regard to these issues, the article provides a case study, one in which we analyse basic education in Communist Hungary, and look for evidence of the commons design principles as outlined in Elinor Ostrom's IAD Framework. Given the complex nature of basic education, we investigate it from three points of view: as a service, as a set of physical structures (e.g. school buildings), and as a complex of organizational structures (e.g. legal and financial arrangements). On the basis of empirical findings we argue that basic education in the Stalinist epoch did not correspond to Ostromian design principles. Basic education, therefore, was not managed in an equitable way, and its geographical accessibility was uneven. During the 'technocratic' Communism of the 1960s, 1970s, and 1980s, the education system underwent important changes. However, though the circle of those who had some impact on the governance of education expanded, most individuals involved with the education system were still excluded. As a result, the commons approach did not become stronger in general, nor did spatial unevenness with respect to access to basic education decrease. The paper finishes with a brief conclusion of our findings and a discussion of some questions for future research.